2001
DOI: 10.3928/0191-3913-20010101-06
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmologic Screening of Deaf Students in Oregon

Abstract: Purpose: To determine the frequency of Usher's syndrome and other ocular disease in students receiving special education services for the deaf in Oregon and to assess the amount of existing ophthalmologic surveillance of this population. A special emphasis was placed on screening for Usher's syndrome. Methods: From 1980-1990, a prospective twocenter visual screening program of 231 deaf students in schools throughout Oregon was conducted using an ophthalmic questionnaire, complete eye examinations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Reports suggest that the prevalence of ocular morbidities and refractive error amongst children with hearing impairment is 5 -90.1% and 7.2 -62.65%, respectively. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Most of the causes of the reported visual impairment are avoidable. Also, studies have reported that children with hearing impairment are at a higher risk of visual impair-ment than children with no impairment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports suggest that the prevalence of ocular morbidities and refractive error amongst children with hearing impairment is 5 -90.1% and 7.2 -62.65%, respectively. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Most of the causes of the reported visual impairment are avoidable. Also, studies have reported that children with hearing impairment are at a higher risk of visual impair-ment than children with no impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of the significant causes of childhood visual impairment and hearing impairment in Sub-Saharan Africa is associated with measles and rubella . 17 There still exists the lack of scientifically rigorous studies that have investigated the prevalence and causes of visual impairment amongst learners living with hearing impairment in sub-Saharan Africa. Therefore, the aim of this scoping review is to evaluate published scientific research studies on the prevalence and causes of visual impairment in children living with hearing impairment in terms of their visual acuity status, causes, interventions provided/suggested and limitations of the studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo cual los señalan que en los servicios de educación especial donde asisten personas con discapacidad auditiva deben reconocer la necesidad del cuidado visual. 14,15 En general, los errores refractivos son el problema ocular más frecuente en niños, con una prevalencia global estimada de 4.6 a 14.9%. 16,17 Pero en niños con discapacidad auditiva puede ocurrir hasta en 60%, 5 como lo observamos en este estudio que fue de 50%.…”
Section: Discussionunclassified
“…Hearing-impaired and deaf individuals rely on their visual senses more than healthy people; therefore, even low degrees of refractive error, if uncorrected, can reduce visual performance and present people with serious problems [ 7 ]. In addition, previous studies that assessed visual disorders among the deaf and hearing impaired demonstrated that the prevalence of refractive errors, amblyopia, strabismus, and low vision among deaf and hearing-impaired children is higher in comparison with their hearing peers [ 3 , 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%